Corneal sensitivity changes in long-term wearing of hard polymethylmethacrylate contact lenses - (:unkn) unknown (KARGER, 1998)
The effect on corneal sensitivity of years of wearing hard contact lenses was evaluated in 20 subjects who had worn polymethylmethacrylate (PMMA) lenses for up to 20 years. An age- and sex-matched group of 20 eyes was used as the control group. It was found that corneal sensitivity diminished significantly in wearers of PMMA contact lenses. This reduction. of corneal sensitivity was found to be most prominent centrally and was markedly related with the duration of PMMA contact lens use. The loss of corneal sensitivity due to wearing contact lenses increases the risk of a silent infection.
Keywords: contact lenses; corneal sensitivity; polymethylmethacrylate